Factors associated with subsequent diabetes-related self-care activities: The role of social support and optimism - Zhao FF; Suhonen R; Katajisto J; Leino-Kilpi H (WILEY, 2022)
Aim This study aimed to explore how social support (external factor), optimism (internal factor) and their interaction associated with diabetes-related self-care activities (DRSCA) over 3 months among people with type 2 diabetes mellitus (T2DM). Design Both questionnaire-based and telephone-based survey were used. The data were collected face to face, the first time by questionnaire and the second time by telephone. Methods One hundred and fifty-five patients completed valid survey questionnaires (response rate was about 70% in the first and 62% in the second round). The association of social support and optimism with subsequent DRSCA was examined after adjusting for demographics and disease information. Results Based on results, optimism was significantly associated with subsequent DRSCA. In the dimensions of social support, objective social support and support use were significantly associated with subsequent DRSCA. The results showed that the mediation of optimism between the dimensions of social support and DRSCA was not significant after controlling for covariates. The results also indicated that social support and optimism played directly an important role in improving diabetes-related self-care activities.